Perancangan dan Implementasi Sistem Informasi Running Text sebagai Media Edukasi dan Komunikasi Warga Dukuh Tanggung - Zaki La Tansa; Aryo Juliansyah; Muhammad Zainuri; In’am Vaviansyah; Nanda Agrandis; Aurora Nur Kusuma; Indah Puji Astuti (Perkumpulan Kualitama Edukatika Indonesia, 2026)
This community service program was conducted to address the communication challenges faced by the partner community in Dukuh Tanggung, Cepoko Village, Ponorogo, which lacked effective media for information dissemination. The program aimed to design and implement a microcontroller-based running text information system to improve the distribution of social, health, and administrative information. The methods included needs assessment, hardware and software design, system installation at a strategic public location, and training and mentoring for community leaders and youth organization members. The results indicated that the running text system significantly improved access to information, with 80% of residents reporting that the system was highly helpful, and 90% of local operators successfully managing the system independently. The integration of the running text display with a 1.5 × 1 meter banner space also enhanced flexibility in delivering both tactical and long-term messages. This program effectively transferred appropriate technology, strengthened community digital capacity, and improved public communication within Dukuh Tanggung. These outcomes suggest strong potential for future development, including web-based integration and broader digital communication innovations for rural communities.